Scaling climate resilience: Local agro-climatic committees reach 6,000 more Cambodian farmers - Swaans, Cornelis; Soksophors, Yim (2024)
An additional 6,000 rice growing smallholder farmers (69% female) from 26 agricultural cooperatives (AC) across four districts of Prey Veng and Takeo provinces in the Lower Mekong Basin (LMB) used seasonal agroclimatic advisories in their planning and decision-making for better climate-risk management. Agroclimatic advisories were developed based on Crop Decision Trees (CDTs) for different climate scenarios through Local Technical Agroclimatic Committees (LTAC).